The Potential of Coconut Shell Waste To Increase the Income Longat Community Mandailing Natal - Enni Sari Siregar; Andyka Zulfahnur Lubis (Cita Konsultindo Research Center, 2022)
The community welfare can be achieved by increasing people's income through the process of economic development. One of the efforts that can be done by utilizing natural resources to use waste into products of economic value. This study aims to examine the potential for processing coconut shell waste into products that have a selling value so that it will affect the level of income. The results showed that the processing of coconut shell waste has the potential to increase people's income. Coconut shell waste is processed into charcoal and liquids smoke that have a high selling value will provide benefits to business actors and also create employment opportunities for the surrounding community, so that the community also gets benefits in the form of additional income. Therefore, the community must be more active in processing goods into new products that have value added to increase people's income and welfare.